(untitled) (Bangladesh Pharmaceutical Journal, 2013)
Ayurvedic system of medicine is a major component of indigenous systems of medicine in Bangladesh. We used an Ayurvedic drug Mrityunjay which is traditionally used for high blood pressure, heart diseases and heartquake. We measured the electrocardiographical (ECG) parameters using an ECG machine (Vet 300, EDAN, China) in rat model before and after administration of the test drug. We observed that, Mrityunjay at high doses (800 ?g/Kg, 1600?g/kg, 3200?g/kg) produced heart blocks and other arrhythmias, but in normal dose (200?g/Kg) it has no serious untoward effects on cardiac muscle. DOI: http://dx.doi.org/10.3329/bpj.v16i1.14503 Bangladesh Pharmaceutical Journal 16(1): 99-105, 2013